Welcome to Fukushima - De Halleux, Alain (Belgium; France; Simple Production, 2013)
In the shadow of the disemboweled reactors of Fukushima, but just outside the evacuation zone, the city of Minamisoma is in suspension. Its future depends on hypothetical and strange decontamination operations as well as the very improbable stabilization of the reactors. After a year of hindsight, it is now time to get out of the excitement of this drama, and watch the transformations that this event will have on Japanese society and also on our societies.
Verzio Film Festival Submission
Keywords: Documentary films